2007
DOI: 10.1038/sj.ki.5002276
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and impaired renal function accompany juvenile obesity: The effect of prenatal diet

Abstract: Obesity has been suggested to have a detrimental impact on kidney structure and function, leading to focal glomerulosclerosis and hypertension. It is also associated with hyperleptinemia and elevated renal sympathetic nerve activity. Prenatal undernutrition promotes postnatal obesity, hypertension, and an altered renal structure and function. In this study, we examined the effects of prenatal nutrient restriction and juvenile obesity in sheep. We found that juvenile obesity led to chronic hyperleptinemia and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 57 publications
(72 reference statements)
9
74
1
Order By: Relevance
“…Similar findings have been reported by other groups (13). In addition, we have shown that adolescent-onset obesity results in marked renal inflammation, apoptosis, and glomerulosclerosis in young adults compared with lean control animals (37). Moreover, when maternal nutrient restriction, from early to midgestation, precedes the onset of obesity in offspring, we see a marked attenuation of these effects in young adults potentially confer-ring an element of renal protection from obesity-related nephropathy (37).…”
supporting
confidence: 75%
“…Similar findings have been reported by other groups (13). In addition, we have shown that adolescent-onset obesity results in marked renal inflammation, apoptosis, and glomerulosclerosis in young adults compared with lean control animals (37). Moreover, when maternal nutrient restriction, from early to midgestation, precedes the onset of obesity in offspring, we see a marked attenuation of these effects in young adults potentially confer-ring an element of renal protection from obesity-related nephropathy (37).…”
supporting
confidence: 75%
“…This situation results, at least in part, from the complexity of the biological processes involved and the challenge of effecting lifestyle changes in activity and dietary intake. At the same time, the causes of the ongoing epidemic of obesity, and the predicted increase in associated renal diseases and CVD, are multifactorial (4) and may be either exacerbated, or reduced, by early dietary exposure (5) . One consistent theme that is apparent from both historical and contemporary studies is that changes in nutrition at specific stages of pregnancy can have very different outcomes (6) .…”
mentioning
confidence: 99%
“…In the heart and in the kidney, significant changes occurred in gene expression between the maternal nutrient-restricted group and their obese controls, principally of factors associated with exposure to cytokines and angiotensin II, possibly suggesting an enhanced adaptation to obesity (40) . However, similar increases in haemodynamic parameters may suggest similar vasomotor afferent responses in both obese groups to the RAS, which also include extensive cell proliferation, particularly of mesangial and proximal tubular endothelial cells (36) .…”
Section: The Combined Effects Of Maternal Nutrient Restriction and Obmentioning
confidence: 99%
“…Between the different animal models studied, the ovine model, due its relatively long pregnancy (145 d) and its ability to produce an offspring of similar weight to human subjects, with fully developed organs, has proven to be useful for increasing the understanding of the effects of changes in maternal diet at specific stages of pregnancy (38) . In different ovine studies, it was observed that a reduction of 50% in maternal food intake up to mid-gestation (days 30 to 80 (145 d to full-term)) produced an offspring of weight similar to those born to control-fed mothers (39,40) . However, as noted in the human Dutch winter cohorts, kidney physiology, blood pressure and fat mass were affected at different points in the offspring's life (39,41,42) .…”
Section: Changes In Maternal Diet During Mid-gestation In Sheep and Tmentioning
confidence: 99%
See 1 more Smart Citation